Evaluasi Peranan Audit Internal pada Penerapan Strategi Anti Fraud - Aisyah Nadiatul Hikmah; Ludovicus Sensi Wondabio (Owner : Riset dan Jurnal Akuntansi, 2023)
This research stems from the enormity of the threat of fraud that can be experienced by any company so it is considered a risk inherent in every company, especially the banking industry. This is shown in the report published by the Association of Certified Fraud Examiners (ACFE) in 2022 which recorded 2,110 cases of fraud in 133 countries across various industries, with the financial or banking industry being the industry victim with the highest number of cases. This research was conducted to evaluate the implementation of anti-fraud strategies in the companies under study to reduce the possibility of fraud occurring and also to identify the role of internal audit in implementing this strategy as one of the company's reliable early detection media. This research was conducted to explore the phenomenon of fraud using a research strategy in the form of a case study type of evaluation at PT. BCD as the company that is focused in this research.. The results of this study explain that PT. BCD, the company under study, has implemented an anti-fraud strategy that at least meets the minimum requirements for its implementation but is unable to instill a culture of the importance of implementing an anti-fraud strategy at every level of position and the company also does not carry out Internal Audit obligations for all aspects of implementation, resulting in weaknesses in the internal control system. Because the application of an anti-fraud strategy alone is not enough to reduce the threat of fraud.